Diffusive dynamics of polymer chains in an array of nanoposts. Issue 1 (1st December 2016) - Ye, Yi; Du, Zhongjie; Tian, Ming; Zhang, Liqun; Mi, Jianguo
Abstract : The diffusion of the head, side, and middle segments in confined polymer chains displays different dynamics in different directions. Abstract : We present a dynamic density functional approach to study polymer chain diffusion in a good solvent in the confinement of a nanopost array. Three key results emerge from our study. First, we show different scaling laws of the chains moving toward, close to, and around the posts. Second, in the flux process of polymer chains, the head, side, and middle segments display different scaling laws. As the chains come in contact with the posts, an enlarged motion discrepancy emerges between the head and middle segments perpendicular to the posts. For instance, the motion of head segments transforms from Zimm to reputation type, whereas the middle segments almost retain the Zimm motion. Third, as the spacing crack between two posts narrows down, a climbing effect along the posts can be clearly observed in the polymer motion.